Anticancer Effects and Mechanisms of Action of Plumbagin: Review of Research Advances. (2nd December 2020) - Yin, Zhenhua; Zhang, Juanjuan; Chen, Lin; Guo, Qingfeng; Yang, Baocheng; Zhang, Wei; Kang, Wenyi
Abstract : Plumbagin (PLB), a natural naphthoquinone constituent isolated from the roots of the medicinal plant Plumbago zeylanica L., exhibited anticancer activity against a variety of cancer cell lines including breast cancer, hepatoma, leukemia, melanoma, prostate cancer, brain tumor, tongue squamous cell carcinoma, esophageal cancer, oral squamous cell carcinoma, lung cancer, kidney adenocarcinoma, cholangiocarcinoma, gastric cancer, lymphocyte carcinoma, osteosarcoma, and canine cancer. PLB played anticancer activity via many molecular mechanisms, such as targeting apoptosis, autophagy pathway, cell cycle arrest, antiangiogenesis pathway, anti-invasion, and antimetastasis pathway. Among these signaling pathways, the key regulatory genes regulated by PLB were NF-k β, STAT3, and AKT. PLB also acted as a potent inducer of reactive oxygen species (ROS), suppressor of cellular glutathione, and novel proteasome inhibitor, causing DNA double-strand break by oxidative DNA base damage. This review comprehensively summarizes the anticancer activity and mechanism of PLB.